2022
DOI: 10.3389/fpls.2021.787877
|View full text |Cite
|
Sign up to set email alerts
|

A System Dynamics Approach to Model Photosynthesis at Leaf Level Under Fluctuating Light

Abstract: Photosynthesis has been mainly studied under steady-state conditions even though this assumption results inadequate for assessing the biochemical responses to rapid variations occurring in natural environments. The combination of mathematical models with available data may enhance the understanding of the dynamic responses of plants to fluctuating environments and can be used to make predictions on how photosynthesis would respond to non-steady-state conditions. In this study, we present a leaf level System Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…These measurements at both LL and HL would exclude a different velocity in Rubisco activation, which is usually considered limiting in the light-saturated phase ( Murchie and Ruban, 2019 ). Nevertheless, it is worth mentioning that in certain conditions MinnGold is found to have a slower induction curve than Eiko ( Salvatori et al, 2022 ), and therefore this needs to be further investigated. Our further measurements related to light transmission through the canopy ( Supplementary Figure S4 ) showed that the changes in transmitted light are faster in Eiko than in MinnGold (but not significantly) and therefore the detected difference in C assimilation during the morning could have been due, to a small extent, to a different adjustment of the leaves inside the canopy as suggested by ( Kaiser et al, 2014 ; Morales et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements at both LL and HL would exclude a different velocity in Rubisco activation, which is usually considered limiting in the light-saturated phase ( Murchie and Ruban, 2019 ). Nevertheless, it is worth mentioning that in certain conditions MinnGold is found to have a slower induction curve than Eiko ( Salvatori et al, 2022 ), and therefore this needs to be further investigated. Our further measurements related to light transmission through the canopy ( Supplementary Figure S4 ) showed that the changes in transmitted light are faster in Eiko than in MinnGold (but not significantly) and therefore the detected difference in C assimilation during the morning could have been due, to a small extent, to a different adjustment of the leaves inside the canopy as suggested by ( Kaiser et al, 2014 ; Morales et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while we found no effect of light fluctuations on biomass accumulation in LL ( Figure 1A ), we measured a further decrease in cumulative C uptake for MinnGold in HL ( Figure 1B ). Leaf level data and models ( Salvatori et al, 2022 ) taken in fluctuating LL confirmed that no difference is expected in such conditions, while the measured reduction in C uptake in MinnGold in HL might be due to several processes, such as lack of acclimation; chloroplasts movements within the leaves ( Kaiser et al, 2014 ; Dutta et al, 2015 ; Semer et al, 2018 ); photoprotective mechanisms to prevent photo-inhibition ( Eberhard et al, 2008 ; Yamori, 2016 ); leaf movement within the canopy ( Gamon and Pearcy, 1989 ; Huang et al, 2014 ; Kaiser et al, 2014 ); different NPQ relaxation upon transition to low light ( Zhu et al, 2004 ; Sakowska et al, 2018 ); and lower NPQ in the low light–high light transitions causing photo-inhibition ( Yamori, 2016 ). Even though our experimental setup was not able to clearly elucidate the role of all these possible mechanisms, combining our results under LL and HL (i.e., photosynthetic rates, leaf movements, induction curves) with previous findings ( Sakowska et al, 2018 ; Ferroni et al, 2020 ) suggests that the truncation in the PSII would impair the global reprogramming of photosynthetic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the Pn of a chlorophyll-deficient Glycine max mutant was similar under steady light but was more responsive to changing light than wild-type Glycine max [ 112 ]. However, Ferroni et al reported that chlorophyll-depleted mutants and wild-type Triticum aestivum had comparable adaptation to changing light [ 113 ].…”
Section: Effects Of Non-environmental Factors On Dynamic Photosynthes...mentioning
confidence: 99%
“…This approach is based on the idea of employing systems modeling to describe the relationship between photosynthesis, environmental factors, and yield (Lammerts van Bueren et al, 2018;Verma et al, 2021). Systems models of plants aim to describe and simulate quantitatively the behavior of a number of plant traits at scales ranging from single cells to whole ecosystems (Salvatori et al, 2022). Such an approach appears to be promising for developing a coherent view of the impact of the many photosynthetic LUE strategies on plant productivity and highlighting specific combinations of environmental and genetic factors that will increase crop yields (Chang et al, 2019).…”
Section: Photosynthesis and Yield Research: Where To Now?mentioning
confidence: 99%